Gambaran Gangguan Muskuloskeletal pada Pembatik di Pos UKK Kapal Sanggat - Indah Permata Sari; Putra Hadi; Safitri Rahayu (Science: Indonesian Journal of Science, 2026)
Musculoskeletal disorders complaints involving the musculoskeletal system are the most common work related health issues. Prolonged work in non ergonomic seated positions can lead to various problems, particulary given that the workers tasks are predominantly performed while seated. This study aimed to assess the prevalence of musculoskeletal complaints among pembatik. A descriptive research design was employed, with the study population consisting of all pembatik at the Kapal Sanggat UKK Post in Seberang Kota Jambi. A purpose sampling method was used to select a sample of ten pembatik. Data collection involved questionnaires, observation, and interviews. The results indicated that musculoskeletal complaints among the pembatik were influenced  by duration of work and working posture the most frequently reported complaints involved the back of the neck, shoulder, and lower back. Its is recomended  that these findings serve as a basis for further research and the development of preventive measures regarding these musculoskeletal issues in the field of physiotherapy.